Sex differences in treatment effects of lecanemab and donanemab: A Bayesian reanalysis of CLARITY-AD and TRAILBLAZER-ALZ2 - Teipel, Stefan J; Tang, Yi; Khachaturian, Ara (Alzheimer's & dementia (New York, N. Y.), 2025)
INTRODUCTION: This study investigated evidence for or against a difference in treatment effect between women and men for lecanemab and donanemab. METHODS: Data were derived from supplementary analyses of the regulatory studies CLARITY-AD (lecanemab) and TRAILBLAZER-ALZ2 (donanemab). Bayes factor functions were used to analyze treatment effects on Clinical Dementia Rating Sum of Boxes (CDR-SB) scores. RESULTS: We found moderate evidence of a lower treatment effect in women than in men for lecanemab (maximum Bayes factor = 5.97), suggesting that the presence of an effect was almost six times more likely than the absence of an effect. For donanemab, there was evidence against a treatment effect difference between women and men. There was evidence of a treatment effect difference between lecanemab and donanemab (maximum Bayes factor = 8.47) in women, but not in men. DISCUSSION: A better understanding of sex differences in treatment efficacy and their causes is urgently needed. HIGHLIGHTS: Lecanemab was six times more likely to be ineffective than effective in women.There was no evidence of a difference between the sexes in the effect of donanemab.Lecanemab and donenamb differed in treatment efficacy in women but not in men.Future trials should include sufficient power for sex related interaction effects.
Keywords: personalized treatment; prespecified secondary analysis; subgroups; treatment efficacy; anti‐amyloid antibodies